Ammonium sulfate denatures transport medium less dependent on guanidinium isothiocyanate and enables SARS-CoV-2 RNA and antigen detection compatibility - Liu, Ge; Xu, Jiapeng; Huang, Yuanyuan; Ye, Wei; Li, Jieyu; Yan, Ran; Luo, Qiting; Zhou, Xinrui; Cai, Yingna; Jiang, Hanfang; Lu, Xiujing; Zheng, Kai; et al. (Frontiers in Microbiology, 2024)
Rapid identification of infected individuals through viral RNA or antigen detection followed by effective personal isolation is usually the most effective way to prevent the spread of a newly emerging virus. Large-scale detection involves mass specimen collection and transportation. For biosafety reasons, denaturing viral transport medium has been extensively used during the SARS-CoV-2 pandemic. However, the high concentrations of guanidinium isothiocyanate (GITC) in such media have raised issues around sufficient GITC supply and laboratory safety. Moreover, there is a lack of denaturing transport media compatible with SARS-CoV-2 RNA and antigen detection. Here, we tested whether supplementing media containing low concentrations of GITC with ammonium sulfate (AS) would affect the throat-swab detection of SARS-CoV-2 or a viral inactivation assay targeting coronavirus and other enveloped and non-enveloped viruses. The effect of adding AS to the media on RNA stability and its compatibility with SARS-CoV-2 antigen detection were also tested. We found that adding AS to the denaturing transport media reduced the need for high levels of GITC, improved SARS-COV-2 RNA detection without compromising virus inactivation, and enabled the denaturing transport media compatible with SARS-CoV-2 antigen detection.